Sistematización del curso teatro contemporáneo 2020-1 “Roxane and Julieth” Una adaptación del clásico “Romeo y Julieta” de William Shakespeare (2021)
In this degree work the lived experience of the 2020-1 Contemporary Theater course is systematized, accounting for the adaptation entitled "Roxane and Julieth" a contemporary version that was created from the dramaturgical text entitled "Romeo and Juliet" by William Shakespeare, In the development of this systematization, the most significant pedagogical processes of the artist teacher in training and the social circumstances where a global crisis was witnessed due to the Covid-19 virus are narrated, because of this classes are retaken virtually.